A 14‐year statistics‐based semi‐idealized modeling study on the formation of a type of heavy rain–producing southwest vortex. (25th March 2019) - Zhang, Yuan‐Chun; Fu, Shen‐Ming; Sun, Jian‐Hua; Fu, Rui; Jin, Shuang‐Long; Ji, Dong‐Sheng
Abstract : On the basis of a 14‐year statistical dataset of the southwest vortex (SWV), 10 long‐lived and heavy rain–producing SWVs are selected for a series of convection‐permitting composite semi‐idealized simulations. After confirming the simulation has reproduced the common salient features of these selected vortices, the general underlying mechanisms for the formation of this type of SWV are investigated. Results show that the SWV formation is characterized by significant unevenness, as the fundamental characteristics and dominant factors for the cyclonic‐vorticity production vary from place to place. Overall, the eastern/western section of SWV mainly features favorable/unfavorable conditions for the cyclonic‐vorticity enhancement. The vorticity budget indicates the convergence‐related horizontal shrinking and convection‐related tilting contribute to the cyclonic‐vorticity enhancement in the SWV's eastern section, whereas in the western section, the terrain‐related tilting and horizontal transport result in the cyclonic‐vorticity reduction. Abstract : On the basis of a 14‐year statistical dataset, the universal mechanisms underlying the formation of a typical type of heavy rain–producing of southwest vortices (SWVs) is derived as the above shows (VAV = vertical advection of vorticity; STR = stretching; TIL = tilting. A bigger size of a sign means larger intensity). The SWV formation features significant unevenness, the eastern/western section of the SWV has favorable/unfavorable conditions for cyclonic‐vorticity enhancement. The horizontal convergence‐related shrinking and convection‐related tilting favor cyclonic‐vorticity enhancement in the SWV's eastern section, whereas in the western section, terrain‐related tilting and horizontal transport cause cyclonic‐vorticity reduction.